Centralized on-site detention (OSD) tank : potential re-use of water harvest implementation in housing / Nurdayana binti Mohamad Suki - Mohamad Suki, Nurdayana (2018)
Stormwater runoff has contributed to floods on the surface of the earth, especially those in dense and urbanized areas. Hence, an urban storm water management solution, On-Site Detention (OSD) tank has been introduced by the government to tackle the issue. The OSD tank may integrate a rainwater harvesting system for the purpose of re-using rainwater as a water supply alternative for occupants in residential areas. By making the tank's stored water reusable and the implementation practical, consumers can generate their own water source to reduce water bills. Therefore, a study on the concept of OSD implementation will be conducted, which focuses on three objectives. Firstly, to understand the concept of OSD. Secondly, to determine the issues and challenges in the perspective of OSD and water harvesting implementation in Malaysia. Lastly, to propose a Centralized system within OSD tank implementation and the potential way to utilize harvested rainwater in housing and residential areas. A desk study will be conducted in finding relevant research to propose a solution that is through the centralized system in OSD application.